Indentation mechanics of layered solids - Zheng, Zuwei (2008)
In this thesis, the Johnson-Kendal-Roberts (JKR) adhesion theory for bulk elastic solids is extended to the adhesion analysis of layered thin film system. A numerical approach to study the identation of layered solids in the presence of adhesion is presented. The infinite element (FE) calculation effectively takes into account both adhesionless and adhesion indentations.